Simple Model for the Theoretical Survey of the Green Roof Thermal Behavior - Morau, Dominique; Tiana, Rakotondramiarana Hery; Ludovic, Andriamamonjy Ando (Journal of Technology Innovations in Renewable Energy, 2013)
A green roof is an option for the improvement of a building thermal comfort. The objective of this work is to compare respective behaviors of a green roof and a concrete watertight roof vis-à-vis external requests in wet tropical zones. The canopy being considered as uniform, the electric analogy method was used to establish the mathematical models associated to both studied systems of roof. Based on these models, a Matlab computing code was worked out. It ensues from simulation results that in diurnal period, the green roof concrete support top face temperature is lower than that of the concrete watertight roof top face, whereas in night-period the opposite occurs. These results which highlight the energy benefit of the green roof are in agreement with the experimental measurement results obtained at the Laboratory PIMENT of the University of La Reunion. Besides, results of sensitivity analysis done with Fourier Amplitude Sensitivity Test enabled to identify a certain number of the most influential parameters of the proposed model. The above mentioned computing code also forms a help tool for the choice of plants to be experimented on the green roof.